2019
DOI: 10.1007/s00359-018-01314-0
|View full text |Cite
|
Sign up to set email alerts
|

Lagenar potentials of the vocal plainfin midshipman fish, Porichthys notatus

Abstract: The plainfin midshipman fish (Porichthys notatus) is a species of marine teleost that produces acoustic signals that are important for mediating social behavior. The auditory sensitivity of the saccule is well established in this species, but the sensitivity and function of the midshipman’s putative auditory lagena are unknown. Here, we characterize the auditory-evoked potentials from hair cells in the lagena of reproductive type I males to determine the frequency response and auditory sensitivity of the lagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 56 publications
(97 reference statements)
0
8
1
Order By: Relevance
“…The asteriscus, which was closest to swim bladder distance, exhibited the highest acceleration among all otoliths. This was different from the findings in sleeper goby ( Dormitator latifrons ) and plainfin midshipman, which showed that the thresholds of the lagenar potentials were higher than those of the saccule (Lu et al, 2003; Lu et al, 2010; Vetter et al, 2019). The difference between lagenar and saccular vibration might be due to the distance from the swim bladder to the otoliths (Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…The asteriscus, which was closest to swim bladder distance, exhibited the highest acceleration among all otoliths. This was different from the findings in sleeper goby ( Dormitator latifrons ) and plainfin midshipman, which showed that the thresholds of the lagenar potentials were higher than those of the saccule (Lu et al, 2003; Lu et al, 2010; Vetter et al, 2019). The difference between lagenar and saccular vibration might be due to the distance from the swim bladder to the otoliths (Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…At frequencies above 200 Hz, when the swim bladder contribution increases, greater local particle motion may be transmitted to the asteriscus, resulting in a stronger motion of this otolith. Note that a recent study on the plainfin midshipman (Porichthys notatus Girard, 1854) [57], a species that lacks an otophysic connection, indicates that auditory thresholds of the lagena (based on sound pressure and particle acceleration) were higher than that of the saccule in the frequency range from 85 to 505 Hz.…”
Section: Otolith Mass and The Type Of Otophysic Connection Apparently Affect Otolith Motionmentioning
confidence: 98%
“…These end organ differences in HC number are likely related to the end organ size of the macular area with the saccule having the largest macular area in general (note, we did not compare the macular areas of the utricle, lagena, and saccule, but the differences in end organ size visually are obvious). Not sur-prisingly, the lagena, which is the smallest end organ, is significantly less sensitive than the saccule and utricle based on HC auditory evoked potentials [Colleye et al, 2019;Vetter et al, 2019;Rogers and Sisneros, 2020]. In addition to having fewer total HCs as we report here, the lagena also has the lowest otolith mass (smallest of the three end organs) and contains an otolith (asteriscus) that is predominantly composed of lighter vaterite [Campana, 1999;Reimer et al, 2016].…”
Section: Discussionmentioning
confidence: 57%